Determination of Japanese Encephalitis Virus (JEV) among Acute Encephalitis Syndrome Cases at Chandrapur, Maharashtra, India: A Serological Study - Kolhe, V. S.; Surpam, R. B.; Munde, B.; Gawande, R.; Bobade, O. (Innovations in Microbiology and Biotechnology Vol. 3, 2022)
The present study was undertaken to make a countable move not only towards the diagnosis of the diseases but also to restrict its future spread in Indian continent. Which will also aid medical practitioners to combat with this metazoonotic disorder. Japanese encephalitis Virus (JEV) a flaviviridae family member (genus Flavivirus) is the main cause of meta-zoonotic viral encephalitis in many Asian countries. The disease was primarily reported in 1952 from Nagpur territory of Maharashtra recording nearly 16 deaths of an unknown viral encephalitis which was later awarded to be JEV; just nearer to Chandrapur reporting the present catastrophes. Amongst total suspected population nearly these 20 males and 22 females were positive. Considering monthly distribution most number of suspected cases were seen in the month of July. Most number of JEV affected population was seen more in the age group of 1 to 5 years of children and with advancement of the age reduction in the number of seropositive cases were observed. Human blood or CSF to be the reservoir Source from which isolation of opportunistic infections could be made possible. Also important role played by vaccinations could also be cross checked in JE epidemic areas. Hence role of JE Vaccine in routine vaccination programme in JEV epidemic areas could also be proved to be beneficial.